The Design-Drawing Relationship in Small Artifacts. Practices, Reflections and Dynamics of Representation for Arthouse Handles (diségno, 2022)
Between theory and practice, this work questions the nature of the handle design, the direct metric relationship between the drawn data, the one thought and, subsequently, realized; between the imaginary data, accessible in the representation, and the real one,on the modality of use of the represented data which also significantly affects the technical-configurative procedures; on the ‘real’ management of planning, formal and executive contents. More specifically, the article on the one hand reconstructs the story of the relationship between drawing and design through the study of the handle artifact from the Bauhaus to the present day, identifying and observing emblematic cases (arthouse handles) intended as fundamental stages in the construction of a dialogic story between project and representation in its double aesthetic and ethical value; on the other hand, it reconstructs an infographic knowledge system oriented to the visualization of design themes linked to the handle artifact through devices which take into account the dynamics of representation of the artifacts and morphological qualities towards hybrid media and narrative forms, within the framework of a research experience based on the encounter between the discipline of design and that of drawing and on experimentation strategies implemented through the methods and codes of representative language in a continuous and lively definition of disciplinary boundaries.
Keywords: handles; design; drawing; representation; taxonomy